Management of Islamic Boarding School Curriculum Integration in Improving the Quality of Madrasah Education: Hubungan Pendidik dan Peserta Didik Dalam Konsep Pendidikan Islam Menurut Abbudin Nata - Anas, Anas; Astutik, Anita Puji (Indonesian Journal of Education Methods Development, 2018)
This research is based on the phenomenon of the relationship between educators and children in the concept of Islamic education which was initiated by Abbudin Nata. so he has a big share in the progress of Islamic education, within the scope of teaching which is the subject of research questions, namely: What is the concept of Islamic education according to Abbudin Nata? How is the application of the concept of Islamic education according to Abbudin Nata? To solve this question, this study uses library research (library research). Because the research here uses literature, the writer examines the concept of Abuddin Nata's thoughts with other people's books. The results of the research show that according to Abuddin Nata, first, Islamic education according to Abuddin Nata is an effort to foster, guide and instruct students who make learning habits accept with sincerity of learning, seeking knowledge for the sake of Allah, consciously and planned to have a personality in accordance with the values ​​of Islamic teachings, namely the Al-Qur'an and Sunnah. Second, the concept of educators according to Abuddin Nata is an Islamic scholar who has a very broad knowledge of Islam based on his experience because it requires educators to be sincere only for Allah SWT, what is the condition of educators to be the most role models for their students. His view of students is that they are creatures that have natural potential and, giving up everything just to learn, pursue knowledge solely because of Allah SWT, being kind to their teachers.